The Role of Psychology in Higher Education Leadership - Mahalli; Sukarman (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Higher education leadership is confronted with increasingly complex challenges arising from globalization, digital transformation, and growing demands for quality assurance. University leaders are expected to demonstrate not only strong managerial and academic competencies but also a sound understanding of the psychological dimensions of individuals and groups within academic organizations. This article aims to examine conceptually the role of psychology in higher education leadership and its implications for leadership effectiveness. A literature review approach was employed, drawing on relevant scholarly sources, including academic books, peerreviewed journal articles, and previous empirical studies on psychology and higher education leadership. The review reveals that psychological competence is critical to effective decision-making, faculty motivation and performance, organizational communication, conflict management, and the practice of transformational leadership in higher education institutions. Accordingly, the integration of psychological competencies into leadership development programs is essential to enhance organizational performance and improve the quality of higher education.